THERMOMINERAL WATERS OF THE DAGINSKY FIELD (SAKHALIN ISLAND): PHYSICAL-CHEMICAL CHARACTERISTICS AND FORMATION CONDITIONS - Valery V. Ershov; Olga A. Nikitenko; Rafael V. Zharkov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
The relevance of the research is determined by the current active exploitation of hydrothermal systems as an alternative energy source using renewable energy resources, for the extraction of rare metals, the development of ecological, health-improving and extreme tourism. Identification of the types of hydrothermal fields, geological conditions and patterns of their formation and modern activity are necessary for a correct assessment of their practical use. Daginsky thermomineral field, the hydrogeochemical features of which not yet well understood, is known in the north of Sakhalin Island. The aim of the work is to obtain new data on the physical-chemical parameters of thermomineral waters of the Daginsky field and to conduct a comparative analysis of the hydrogeochemical characteristics of its different sites (North, Central, South), and also to propose a model explaining the origin and patterns of formation of the chemical composition of the research waters. Objects: thermomineral waters of the Daginsky field (Sakhalin Island). Methods. Chemical analytical researches of the thermomineral waters were carried out at the Center for the Collective Use of the Institute of Marine Geology and Geophysics Far Eastern Branch Russian Academy of Sciences. The electrical conductivity of the research waters was determined by conductometric method, pH was determined by the potentiometric method. The surface temperatures of the waters in the thermomineral springs were measured using a digital thermometer. The concentrations of Na+, K+, Ca2+, Mg2+, Li+, Cl–, SO42–, NO2–, NO3–, Br– were determined by the method of ion chromatography; concentrations of HCO3– and CO32– were determined by the titrimetric method; content of the boron and silicon were determined by the spectrophotometric method. The content of organic and inorganic carbon, as well as total nitrogen was determined by high-temperature catalytic oxidation. Reservoir temperatures of thermomineral waters were calculated using hydrochemical geothermometers – K-Mg, Na-K, Mg-Li, Na-Li, SiO2. Results. The article presents the results of modern hydrogeochemical researches of the Daginsky field, conducted from 2014 to 2019. It has been established that spatial hydrogeochemical heterogeneity is observed on the territory the field. This heterogeneity is expressed in the differences in the physical-chemical characteristics of thermomineral waters (the surface temperatures, the value of total dissolved solids, and the concentration of main components of the water-salt composition) in its different sites (Northern, Central and Southern). The waters in the three sites have the same Cl-Na composition, but in the Southern and Central sites they have higher concentrations of Na+, HCO3–, Si, and in the Northern – K+, Ca2+, Mg2+, SO42–, B. The waters of the springs of the Northern site are also characterized by higher salinity (2–8 times) and lower values of surface temperatures (mainly by 10–15 °С) compared to the waters of the springs of the Southern and Central sites. Based on the obtained hydrogeochemical data, a model for the formation of thermomineral waters of the Daginsky field is proposed, which includes three «end members». According to this model, the formation of the research waters occurs as a result of mixing of mature brackish groundwaters of the North Sakhalin artesian basin, which are presumably developed in the lower part of the Nutovskaya suite, with modern fresh meteoric waters during their infiltration in the feeding area of the artesian basin, as well as salty seawaters of the Nyisky Bay in the area of discharge of thermomineral waters. The share of fresh infiltration waters of meteoric genesis in thermomineral waters can range from 15 to 80 %, the share of seawaters can be up to 30 %. The processes in the «water–rock–gas–organic matter» system have a significant impact on the chemical composition of the research waters: sulfate reduction, cation exchange and sorption-desorption. Reservoir temperatures for the Daginsky field are predominantly 60–100 °С, which corresponds to a depth of about 2–3 km.